2022
DOI: 10.1021/acsomega.2c01029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Talc Particle Size in Detergents for Fruits and Vegetables on the Ability to Remove Pesticide Residues

Abstract: Detergents containing abrasive talc particles for washing fruits and vegetables were designed and investigated. Detergent prototypes were developed with the following composition: 40% talc particles, 1.5% surfactants, 5% ethyl alcohol, 1% sodium citrate, 1% sodium carbonate, 1.5% glycerin, and 0.5% preservative. Xanthan gum (0.5% concentration) was used as a viscosity modifier to stabilize the dispersion of talc particles. Three types of detergent prototypes were prepared, differing in the size of the talc par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[5][6][7][8] Consequently, there is a worldwide emphasis on research into effective methods of removing pesticide residues from various fruits and vegetables. [9][10][11][12][13][14][15] The conventional household practice often involves washing produce with tap water [16] but this approach can be ineffective, particularly for hydrophobic pesticides. [17][18] The need to protect consumers from the hazardous effects of pesticides requires the investigation of effective pesticide removal strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Consequently, there is a worldwide emphasis on research into effective methods of removing pesticide residues from various fruits and vegetables. [9][10][11][12][13][14][15] The conventional household practice often involves washing produce with tap water [16] but this approach can be ineffective, particularly for hydrophobic pesticides. [17][18] The need to protect consumers from the hazardous effects of pesticides requires the investigation of effective pesticide removal strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a worldwide emphasis on research into effective methods of removing pesticide residues from various fruits and vegetables [9–15] . The conventional household practice often involves washing produce with tap water [16] but this approach can be ineffective, particularly for hydrophobic pesticides [17–18] …”
Section: Introductionmentioning
confidence: 99%
“…The performance of laundry detergents is categorized as 'primary' (removing stains) and 'secondary' (preventing redeposition) [2]. Sodium carbonate (Na 2 CO 3 ) is a common non-phosphorus detergent aid with excellent calcium removal and stain removal properties [3,4]. Meanwhile, it poses difficulties in hard water conditions due to the formation of insoluble calcium carbonate deposits on the fabric surface [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pugliese et al (2004) reported that a soaking solution containing glycerin, ethanol and sodium lauryl sulfate showed the ability to remove almost 50% of pesticide residues, while aqueous solutions containing citric acid, hydrogen peroxide, potassium permanganate, sodium pyrosulfite, sodium hypochlorite, and urea appeared not to be more effective compared to washing with pure water. Wasilewski et al (2022) developed a special abrasive paste based on talcum particles for washing fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%